Environmental Sociology - Bandy, Joe (TRAILS: Teaching Resources and Innovations Library for Sociology, 2010)
Environmental sociology is a field that provides insight into the complex social processes which define, create, and indeed threaten our natural environment. By discussing issues of science and technology, popular culture, economics, urbanization, racial and gender relations, as well as social movements, this course will reach a borad understanding of environmental issues and philosophy. More specifically, this course will investigate the relationships between various environmental and social problems, as well as the many political ideologies, philosophies, and movements that have continually redefined how we think of nature and sustainability.